Desenvolvimento e validação de um método quimométrico para a determinação de hidroclorotiazida em formulação farmacêutica usando medidas de reflectância difusa no infravermelho próximo - (:unkn) unknown (Universidade Estadual de Goiás, 2012)
In the present work it was developed and validated a new multivariate diffuse reflectance near infrared method for direct determination of hydrochlorothiazide in powder pharmaceutical samples (tablets). The best partial least squares (PLS) model was obtained in the spectral region from 1640 to 1780 nm, with mean centered data preprocessed by first derivative and Savitzky-Golay smoothing followed by vector normalization. This model was built with 4 latent variables and provided a root mean square error of prediction (RMSEP) of 1.7 %. The method was validated according to the appropriate regulations in the range from 21.25 to 29.00 mg of hydrochlorothiazide per 150 mg of powder (average mass tablet), by the estimate of figures of merit, such as accuracy, precision, linearity, analytical sensitivity, capability of detection, bias and residual prediction deviation (RPD). The concept of net analyte signal (NAS) was used to estimate some figures of merit and to plot a pseudo-univariate calibration curve. The results for determinations in powdered manufactured tablets were in agreement with those of the official high performance liquid chromatographic method (HPLC). Finally, the method was extrapolated for determinations in intact tablets, providing prediction errors smaller than ± 9%. The developed method presented the advantage of being about fifteen times faster than the reference HPLC method.
Keywords: Hidroclorotiazida; Quimiométrico; Reflectância difusa; Infravermelho; Calibração multivariada; CIENCIAS EXATAS E DA TERRA::QUIMICA